OKN‐007 decreases tumor necrosis and tumor cell proliferation and increases apoptosis in a preclinical F98 rat glioma model. Issue 6 (29th April 2015) - de Souza, Patricia Coutinho; Balasubramanian, Krithika; Njoku, Charity; Smith, Natalyia; Gillespie, David L.; Schwager, Andrea; Abdullah, Osama; Ritchey, Jerry W.; Fung, Kar‐Ming; Saunders, Debra; Jensen, Randy L.; Towner, Rheal A.
Abstract : Background: Glioblastoma is a malignant World Health Organization (WHO) grade IV glioma with a poor prognosis in humans. New therapeutics are desperately required. The nitrone OKN‐007 (2, 4‐disulfophenyl‐PBN) has demonstrated effective anti‐glioma properties in several rodent models and is currently being used as a clinical investigational drug for recurrent gliomas. We assessed the regional effects of OKN‐007 in the tumor necrotic core and non‐necrotic tumor parenchyma. Methods: An F98 rat glioma model was evaluated using proton magnetic resonance spectroscopy ( 1 H‐MRS), diffusion‐weighted imaging (DWI), morphological T2‐weighted imaging (T2W) at 7 Tesla (30 cm‐bore MRI), as well as immunohistochemistry and microarray assessments, at maximum tumor volumes (15–23 days following cell implantation in untreated (UT) tumors, and 18–35 days in OKN‐007‐treated tumors). Results: 1 H‐MRS data indicates that Lip0.9/Cho, Lip0.9/Cr, Lip1.3/Cho, and Lip1.3/Cr ratios are significantly decreased (all P  < 0.05) in the OKN‐007‐treated group compared with UT F98 gliomas. The Cho/Cr ratio is also significantly decreased in the OKN‐007‐treated group compared with UT gliomas. In addition, the OKN‐007‐treated group demonstrates significantly lower ADC values in the necrotic tumor core and the nonnecrotic tumor parenchyma (both P  < 0.05) compared with the UT group. There was also an increase in apoptosis following OKN‐007 treatment ( P  < 0.01) compared with UT. Conclusion: OKN‐007 reduces both necrosis and tumor cell proliferation, as well as seems to mediate multiple effects in different tumor regions (tumor necrotic core and nonnecrotic tumor parenchyma) in F98 gliomas, indicating the efficacy of OKN‐007 as an anti‐cancer agent and its potential clinical use. J. Magn. Reson. Imaging 2015. J. MAGN. RESON. IMAGING 2015;42:1582–1591.